Kajian Komparatif Instrumen Supervisi dalam Kurikulum 2013 dan Kurikulum Merdeka - Eko Rubiyantoro; Novan Ardy Wiyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study comparatively examines academic supervision instruments in Kurikulum 2013 and Kurikulum Merdeka using a qualitative approach and document analysis. Academic supervision plays a crucial role in enhancing teaching quality and teacher professionalism through systematic guidance and evaluation. Kurikulum Merdeka, which emphasizes flexible and student-centered learning, requires supervision instruments that are more adaptive, reflective, and supportive of teacher innovation compared to the more structured and normative instruments of Kurikulum 2013. Findings reveal significant differences in focus, orientation, instrument form, teacher involvement, and supervision flexibility. Kurikulum 2013 instruments are more formal and evaluative, while those for Kurikulum Merdeka focus on professional development and continuous reflection with a collaborative approach. The implications are vital for developing relevant and effective supervision instruments to support successful implementation of both curricula and improve educational quality in schools.